Effects of 6-week explosive hip thrusts vs. explosive half squats in female high school soccer players - Millar, N. (California State University, 2018)
Recent literature has highlighted the necessity to include specific strength training that mimic on-field demands that lead to successful performance. Few studies have examined specific strength training in female athletes. Therefore, the aim of this study was to examine whether explosive hip thrusts (HT) or explosive half squats (SQ) would improve strength, sprinting, agility, jumping, or kicking performance in female high school soccer players. The participants were randomized into two groups: HT (n = 6, age: 15.7 ± 0.8 years, height: 162.6 ± 5.8 cm, mass: 56.3 ± 6.4 kg) or SQ (n = 8, 15.3 ±.71 years, height: 159.1 ± 7.2 cm, mass: 56.7 ±6.7 kg). The 6-week training program required each group to perform their respective exercise twice-a-week during in-season. A two-way repeated measures ANOVA revealed a main effect for HT and SQ strength, broad jump and kicking distance; however, no interactions were present for any of the dependent variables. Furthermore, ANOVA revealed HT provided a notable effect size for kicking distance when compared to the SQ, indicating greater possible carryover. The present study showed HT and SQ produced similar increases in performance, with no statistical advantage over the other. Therefore, it is recommended to include one of these exercises within a strength training program. Inclusion of either exercise may depend on coaching or athlete preference, specificity, and/or availability of equipment.